Construction of a temperature-controlled chamber - Kassem, Mohammad; Hjalmarsson, Samuel (My University, 2023)
This degree project aims to construct a temperature-controlled chamber for evaluating the strength and elongation of conveyor system components at temperatures spanning from room temperature to 100 °C. The objective is to improve the quality of the company’s products by testing their conveyors’ mechanical properties, including tensile strength, yield strength, and ductility, at various temperatures. This report describes the construction of a temperature-controlled chamber with a temperature range of ambient to 100 °C, including its heating element, temperature sensor, control system, insulation, air circulation ventilation, and safety features. Also discussed are the materials used to construct the chamber, such as ceramic insulation and aluminum box. In its conclusion, the report highlights the project’s limitations, namely the insufficient budget for the chamber’s construction, potentially leading to inaccurate temperature regulation, and the fact that the chamber will be partially open, resulting in temperature fluctuations